Mathematics 1001 : absolutely everything that matters in mathematics in 1001 bite-sized explanations - Elwes, Richard (Buffalo, New York : Firefly Books, 2014)
Provides a practical reference to all aspects of mathematics, using clear explanations of such key mathematical concepts as analysis, logic, metamathematics, and mathematical physics.--
Numbers -- Geometry -- Algebra -- Discrete mathematics -- Analysis -- Logic -- Metamathematics -- Probability & statistics -- Mathematical physics -- Games and recreation.
Includes index.
500-599
Keywords: Mathematics; Mathematics